The use of household expenditure surveys for the assessment of food insecurity - Smith, Lisa C. (Food and Agriculture Organization of the United Nations, 2002)
This paper explores the use of household expenditure surveys for assessing food insecurity among people in developing countries. The main objective of the paper is to lay out the background information needed for assessing the reliability, validity and practical usefulness of measures of food insecurity obtained from such surveys. From this standpoint, it finds them to have four main strengths. The first is that they are a source of multiple, policy relevant and valid measures. These are: (a) household calorie insufficiency; (b) the percent of expenditures on food, a measure of vulnerability to food insecurity; and (c) dietary diversity, a measure of diet quality. The second strength is that they allow multi- level monitoring and targeting. The measures can be used to calculate within-country, national, regional and developing-world wide prevalences of food insecurity and for monitoring how these change over time. Because the food data are matched with various demographic characteristics of households they can be used to identify who the food insecure are as well. The third strength is that they allow causal analysis for identifying actions to reduce food insecurity, information that is vital to policy makers and program designers intending to reduce food insecurity. Finally, given that food insecurity manifests itself at household and individual levels, as the data on expenditures are collected directly from households themselves, they are likely to be more reliable than those derived from data collected at more aggregate levels. The main weakness of household expenditure surveys for the purposes of measuring food insecurity are that they are currently not undertaken on a regular basis in all developing countries, data collection and computational costs in terms of time, financial resources, and technical skill required are quite high, data are not collected on the access to food of individuals within households and, while reasonably reliable estimates of food insecurity can be obtained, estimates can be biased due to various systematic, non-sampling errors.-- Author's Abstract